"Hamlet", "Macbeth", Anantanarayanan’s "The Silver Pilgrimage" and A Touch of Occidentalism - Kaul, Mythili (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
The article focuses on an encounter with Shakespeare in an unusual place, a novel set in medieval India, where Shakespeare is viewed and assessed by an Indian audience, by Indian listeners, through principles of classical Indian art and thought. Such an encounter creates a sense of incongruity, an incongruity that is cultural, philosophical and aesthetic, but at the same time leads to startling perspectives and new and fresh insights. The novel does not privilege one culture over another but the listeners do and we have a brilliant piece of comic writing where the humour derives from the one-sidedness of their perceptions, their “occidentalism”, their easy assumption of the superiority of their belief system over the “other”. The Silver Pilgrimage thus provides not only a stimulating perspective on two Shakespearean tragedies from the point of view of Sanskrit poetics and Indian thought, but also a gentle expose of the limitations of this point of view, and the cultural chauvinism that lies behind it.